IL-12 immunotherapy of minimal residual disease in murine models of HPV16-associated tumours: induction of immune responses, cytokine production and kinetics of immune cell subsets - Indrová, Marie; Bieblová, Jana; Bubeník, Jan; Reinis, Milan (International journal of oncology, 2008)
We have established animal models of HPV16-associated tumours with distinct levels of MHC class I expression. This model was used for examination of immune responses, production of cytokines and kinetics of immune cell subsets after IL-12 therapy of minimal residual tumour disease induced by CBA-4A (cyclophosphamide derivative) treatment. Upregulation of cytokine production was detected, compared to control animals without tumours. No differences in Th1/Th2 polarization of the immune responses after immunotherapy in animals bearing tumours with different surface expression of MHC class I molecules were observed. In the spleens of TC-1 (MHC class I+) but not of TC-1/A9 (MHC class I-) treated tumour-bearing animals, the cytotoxic CD8+ cells detectable in 51Cr microcytotoxicity assay, were found. In the spleens of TC-1/A9 but not of TC-1 tumour-treated animals, the NK activity measured as the lysis of NK-sensitive YAC-1 targets was detected. Down-regulation of the CD4+ and CD8+ subpopulations in spleens of tumour-bearing animals were not restored after therapy. The percentage of CD25+/CD4+ T regulatory (Treg) cells in lymph nodes remained unchanged. The cytoreductive chemotherapy led to strong upregulation and accumulation of immunosuppressive immature myeloid Gr-1+/CD11b+ cells (IMC) in the spleens of treated animals. The accumulation of Gr-1+/CD11b+ cells was significantly decreased after subsequent IL-12 immunotherapy. These data suggest that elimination of IMC after IL-12 immunotherapy may be responsible for the improvement of antitumour responses after adjuvant IL-12 vaccination for the treatment of CMRTD.
Keywords: Human papillomavirus 16; Interleukin-2 Receptor alpha Subunit; regulace genové exprese u nádorů; imunitní systém; cytokiny; interleukin-12; Immune System; Immunotherapy; zvířata; myši; Mice; Kinetics; Lymph Nodes; lymfatické uzliny; CD4-Positive T-Lymphocytes; protinádorové vakcíny; Interleukin-12; Cancer Vaccines; Cytokines; Neoplasms; receptor interleukinu-2 - alfa-podjednotka; CD4-pozitivní T-lymfocyty; nádory; Animals; Gene Expression Regulation, Neoplastic; imunoterapie; Disease Models, Animal; lidský papilomavirus 16; kinetika; modely nemocí na zvířatech